Pengujian Ekstrak Daun Pepaya (Carica papaya L.) sebagai Insektisida Nabati dalam Mengendalikan Larva Plutella xylostella L. pada Tanaman Pakcoy (Brassica rapa L.) (JURNAL ENFIT : Entomologi dan Fitopatologi, 2023)
P. xylostella is one of the main pests on pakcoy plants when the population number is high the larvae eat all the leaves and leave only the bones of the leaves causing severe dameg. This study aims to determine the effect of using papaya (C. papaya) leaf extract on mortality of P. xylostella larvae. The research was designed using Completely Randomized Design (CRD), consisting of four (4) treatments and four (4) replications A : extract concentration 70 % (70 milliliters of papaya leaf extract + 30 milliliters of water), B : extract concentration 60 % (60 milliliters of papaya leaf extract + 40 milliliters of water), C : extract concentration 50 % (50 milliliters of papaya leaf extract + 50 milliliters of water), K : concentration 0%. Observation show that K treatment with a concentration of (0 %) is known not to show an average mortality, compared to treatment C (50 %) it is known that the average mortality in each replication is 56,25 %, on treatment B (60  %) it is known that the average mortality in each replication is 67,5 %, and on treatment A (70 %) it is known that the average mortality in each replication is 86,25 %. From the results of research testing  papaya  (C. papaya) leaf  extract  as a  botanical insecticide in  controlling  P. xylostella larvae on pakcoy plants, the mortality of P. xylostella larvae was highest in treatment A concentration (70%) mortality of P. xylostella was 86% and the lowest was in treatment C concentration (50%) P. xylostella larvae mortality was 56%.